TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN KARENA PENGARUH LABEL DAN IKLAN SECARA ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Muhammad Ranni; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The tendency of consumptive society is a land as well as a challenge forbusiness actors to market as many products of goods and services. One tool that isoften used by businesses to market their products is by advertising. According to LawNo. 8 of 1999 on Consumer Protection, activities of the introduction or disseminationof information on goods and / or services, to attract the interest of the consumer ofthe consumer to the goods and / or services that will be and are being traded.The problem faced by consumers is not only when buying an electronic itemor clothing for them to use and it is not perfect (like there is a defect), but also theproblem if the electronic goods or clothing is already in a state that is broken or notas expected in the advertisement, the negligence of business actors who neglect tocheck the goods before they are sent to the consumer, therefore it is very necessaryawareness from all parties, consumers, and the parties of online businessmen aboutthe importance of responsibility for the damage of goods before the electronic goodsare in the hands of the buyer.This type of research can be categorized in the type of normative legalresearch, the legal principle used as the object of the problem in the study is theprinciple contained in the criminal justice system, that a judge should be able toconsider the facts of the trial to create a sense of justice.data source used consistingof legal materials primary, secondary law materials, and tertiary legal materials,data collection techniques in this study by literature review method, after the datacollected and then analyzed to be drawn conclusions.Keywords: Responsibility - Business Actor - Consumer Protection